The significance of microsatellite instability in colorectal cancer after controlling for clinicopathological factors. Issue 9 (March 2018) - Kang, Sanghee; Na, Younghyun; Joung, Sung Yup; Lee, Sun Il; Oh, Sang Cheul; Min, Byung Wook
Abstract : Abstract: The colorectal cancer (CRC) patients with microsatellite instability (MSI) have distinct clinicopathological characteristics consisting of factors predicting positive and negative outcomes, such as a high lymph node harvest and poor differentiation. In this study, we measured the value of MSI as a prognostic factor after controlling for these discrepant factors. A total of 603 patients who underwent curative surgery for stages I to III colorectal cancer were enrolled. The patients were divided into microsatellite instability high (MSI-H) and microsatellite stable/microsatellite instability low (MSS/MSI-L) groups. Propensity score matching was used to match clinicopathological factors between the 2 groups. MSI-H patients had a high lymph node harvest (median: 31.0 vs 23.0, P <  .001), earlier-stage tumors ( P <  .001), advanced T stage (89.3% vs 74.0%, P =  .018), and poor differentiation (19.6% vs 2.0%, P <  .001). Survival analysis showed better survival in the MSI-H group, but the difference was not statistically significant ( P =  .126). Propensity score matching was performed for significant prognostic factors identified by Cox hazard regression. After the matching, the survival difference by MSI status was estimated to be larger than before, and reached statistical significance ( P =  .045). In conclusion, after controlling for pathological characteristics, MSI-H could be a potent prognostic factor regarding patient survival.